2018
DOI: 10.1016/j.cels.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape of Metabolic Variation across Tumor Types

Abstract: Tumor metabolism is reorganized to support proliferation in the face of growth-related stress. Unlike the widespread profiling of changes to metabolic enzyme levels in cancer, comparatively less attention has been paid to the substrates/products of enzyme-catalyzed reactions, small-molecule metabolites. We developed an informatic pipeline to concurrently analyze metabolomics data from over 900 tissue samples spanning seven cancer types, revealing extensive heterogeneity in metabolic changes relative to normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 70 publications
3
110
0
Order By: Relevance
“…For example, Lukk et al 28 integrated thousands of microarray files to compile a map of human gene expression. In metabolomics, Reznik et al 29 used MS data from eleven studies to measure the extent of metabolic variation across tumours. A similar trend is starting to be observed in proteomics, where reuse of public datasets is becoming increasingly popular, with multiple applications 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lukk et al 28 integrated thousands of microarray files to compile a map of human gene expression. In metabolomics, Reznik et al 29 used MS data from eleven studies to measure the extent of metabolic variation across tumours. A similar trend is starting to be observed in proteomics, where reuse of public datasets is becoming increasingly popular, with multiple applications 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…This might suggest that they tend to play more significant roles than others in the associated metabolic pathways under many different conditions. For example, lactate, taurine, methionine, and acetylcarnitine were recently found to be more frequently differentially abundant in tumors compared to normal tissues across different cancer types (Reznik et al, 2018). Our study offers a systematic guideline and a reference point in targeted metabolomics analysis by either RPLC-Pos-dMRM or HILIC-Neg-dMRM method for more reliable biological interpretations without sample-dependent optimization of the LC-MS system.…”
Section: Resultsmentioning
confidence: 83%
“…A metanalysis of curated data from clinical metabolic profiling studies in cancer patients confirmed well‐known increases in glycolytic metabolites and also unveiled unprecedented changes in other metabolites such as ketone bodies and amino acids (such as histidine and tryptophan) . Another extensive computational analysis of metabolomics data from 900 tissue samples covering >900 metabolites revealed several polyamines and kynurenines being associated with several aggressive tumor types …”
Section: Opportunities Beyond Warburg's Effect Glycolysis Lactate Mmentioning
confidence: 79%